KAJIAN ETNOFARMASI PENGGUNAAN TUMBUHAN OBAT SEBAGAI ALTERNATIF PENGOBATAN DIARE OLEH MASYARAKAT SUKU OSING DUSUN KRAJAN - Septa, Amira; Hartono; Dian Anggraini, Truly (Jurnal Farmasi (Journal of Pharmacy), 2023)
Diarrhea is a disease that is still a health problem worldwide, including Indonesia. Diarrhea is included in the top 10 diseases that still occur frequently and is ranked 5th in the Osing Tribe. The Osing tribe community treats diarrhea by utilizing plants as medicinal plants that are used from generation to generation. This study was conducted to determine the use of ethnopharmaceuticals in the Osing tribe as a preliminary study for the development of traditional medicine by the Osing tribe as a standardized herbal medicine or phytopharmaca. This research is a descriptive study using qualitative methods with snowball sampling techniques through open- ended interviews with filling out informant information sheets and involving 22 community informants from the Osing tribe, Krajan Hamlet, Kemiren, Glagah, Banyuwangi, East Java. The results of ethnopharmaceutical research in the Osing tribe showed that there were 8 types of plants used for the treatment of diarrhea. Analysis using ICF (Informant Consensus Factor) with a result of 0.6 means that the plant is trusted and used as a hereditary treatment of diarrhea treatment. In the PPV (Plant Part Value) value analysis, which is to calculate the part of the plant used, the results obtained were 50% of the leaves, 23% of the fruit, 27% of the rhizome. Fidelity Level (FL) to determine the type of plant that is most often used in treating diarrhea with the highest result of 100% from among others Guava (Psidium guajava L.) and Cassava (Manihot esculenta).